1995
DOI: 10.1016/0735-1097(95)00354-1
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of programmed ventricular stimulation in patients with bifascicular block: A prospective study of patients with and without syncope

Abstract: The inducibility of ventricular arrhythmias is high in patients with bifascicular block and of the same magnitude in patients with and without a history of syncope. Clinical events during follow-up were not predicted by programmed ventricular stimulation in either of the two groups. The finding of inducible ventricular arrhythmia in patients with bifascicular block should therefore be interpreted with caution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0
2

Year Published

1998
1998
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(39 citation statements)
references
References 31 publications
0
37
0
2
Order By: Relevance
“…17 Moreover, LBBB heightens the risk of life-threatening ventricular arrhythmias and sudden death. 18,19 Given these premises, the high percentage of new-onset LBBB after TAVI spurred interest into whether this conduction disturbance could be associated with a worse prognosis after transcatheter procedures. The present data, from the largest registry to specifically evaluate this question, suggest that new-onset LBBB after TAVI is not associated with a worse prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…17 Moreover, LBBB heightens the risk of life-threatening ventricular arrhythmias and sudden death. 18,19 Given these premises, the high percentage of new-onset LBBB after TAVI spurred interest into whether this conduction disturbance could be associated with a worse prognosis after transcatheter procedures. The present data, from the largest registry to specifically evaluate this question, suggest that new-onset LBBB after TAVI is not associated with a worse prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…This theory is supported by electrophysiological studies of patients with bifascicular block, in whom sustained monomorphic ventricular tachycardia was induced exclusively in patients with a previous myocardial infarction. 47 Furthermore, McAnulty et al 3 followed up 554 patients with bundle-branch block and noticed an increased risk of sudden death due not to bradyarrhythmias but rather to tachyarrhythmias and myocardial infarction.…”
Section: Mortalitymentioning
confidence: 99%
“…In patients with negative electrophysiological studies, Link et al 2 observed development of stable AV block in 18% (after 30 months) and Gaggioli et al 3 in 19% (after 62 months) of patients, thus suggesting that some results are false negatives; the syncope recurrence rate was 19% after 2.2 years in one study 4 and Ϸ40% after 3 years in another 2 ; mortality was generally low. 2,4,5 A significant problem in evaluating syncope and bifascicular block is the transient nature of high-degree AV block and the long interval sometimes required to document it electrocardiographically. An implantable event monitor has recently become available and has been validated in patients with unexplained syncope.…”
mentioning
confidence: 99%